Design And Analysis Of Chainless Transmission Electric Bicycle - et. al., Mr. V. Kondusamy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With increasing in an air pollution and scarcity of fuels (petrol and diesel), electric bikes were playing an important role in this new era. E-bikes were eco-friendly and cost effective for transportation. The demand and constantly increasingly of petrol and diesel cost has made engineers to think for new source of energy for transportation. Electric vehicles gave a breakthrough solution to satisfy the needs required but the cost of electric bikes or e-bikes were too high that normal people cannot afford it easily. In order to fill that gap that everyone to afford an electric bike, this project aimed to design an electric bike. In this project, mainly to reduce the manufacturing cost the electric bike is converted the normal bicycle to an electric bike; the project work designed it in the manner it can be propelled through both manual and electric drive called as e-cycle or hybrid bicycle. In addition to this conversion, an attempt has been done to design this hybrid bicycle without chain, i.e.: gear and shaft mechanism for transmitting the power. Own frame has been designed for the e-cycle which can be used for load carrying purpose also. Frame was designed using solid works and with the help of analyses this project came to the conclusion to use AISI 4130 as a frame material for this hybrid cycle.